2011
DOI: 10.1118/1.3533940
|View full text |Cite
|
Sign up to set email alerts
|

Application of thermography for the assessment of allergen‐induced skin reactions

Abstract: It was demonstrated that the thermographic measurements supplemented by the mathematical model offer a new approach to the quantification of allergen-induced skin reactions. Despite the applied simplifications, the proposed model reflected properly the mechanism of heat generation during skin prick test. Moreover, the continuous recording of the skin temperature represents an additional possibility to investigate the mechanism of the allergic reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 38 publications
(31 reference statements)
0
21
0
Order By: Relevance
“…The inter-subject variability of the parameter can be considered as a confirmation that the immediate allergic response is a highly individual-dependent process, but its value can reflect the skin reactivity. Previous studies have confirmed that histamine migration rate is also parameter responsible for the maximal radius of the heated region (correlation coefficient = 0.85) [12,13]. A comparison of the histamine migration rate with age of patients seems to be interesting (Fig.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…The inter-subject variability of the parameter can be considered as a confirmation that the immediate allergic response is a highly individual-dependent process, but its value can reflect the skin reactivity. Previous studies have confirmed that histamine migration rate is also parameter responsible for the maximal radius of the heated region (correlation coefficient = 0.85) [12,13]. A comparison of the histamine migration rate with age of patients seems to be interesting (Fig.…”
Section: Discussionmentioning
confidence: 87%
“…The above rigorous analysis is not still satisfying because it does not allow to full explanation of about 10 % misinterpreted cases by SPT method. At this point very useful was the model analysis of thermograms which provides opportunity to determine the migration rate of the basic mediator of allergic reactionhistamine (v) [12,13]. Temporal acquisition of control histamine response allows estimating the migration rate of histamine (v) in the skin (average v = 0.013 ± 0.010 mm/ s, range: (0.007-0.041) mm/s).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…• estimating the blood flow within and around the wheal area [13], • estimating electrical impedance [14], • using thermography [15], • using digital photography [16], • and carrying out 3-D scanning [17].…”
Section: Basics On the Skin Prick Test Methodsmentioning
confidence: 99%